ANALISIS STABILITAS TIMBUNAN TANAH DENGAN PERKUATAN GEOTEXTILE MENGGUNAKAN SOFTWAREPLAXIS (Studi Kasus Pembangunan Jalur Ganda Antara Solo Balapan – Kadipiro - Kalioso) - iwan ristanto, Iwan Ristanto; Akhbar Romadhoni , Dimas; Agung Wibawa, Satria (Inisiasi, 2024)
This research aims to determine the stability of embankments without reinforcement and with reinforcement and the amount of settlement that occurs in accordance with the SNI geotechnical standard 8460 of 2017. The research location is in KM. 96 + 400 to 104 + 900 between Solo Balapan – Kadipiro – Kalioso. The analysis was carried out using Plaxis 2D Software version 8.6 without reinforcement, a safety factor value of 1.2 was obtained, where the result was below 1.5, which did not comply with the requirements of SNI 8460:2017 article 7.5.5. as well as a 30 day decline of 1,707 cm, a 100 day decline of 1.6 41cm and a 365 day decline of 1,691 cm. So it can be concluded that the embankment at that location is unstable. For this reason, additional geotextiles are added as reinforcement, after adding geotextiles. In the analysis of the embankment at KM 98 + 550 with the addition of embankment reinforced with geotextile, manual calculation results were obtained with a total of 5 layers of geotextile. The minimum geotextile length is 2.338 m and the stability of the bearing capacity is SF = 4.37 > 1.5. For embankment analysis at KM 98 + 550 after adding geotextile reinforcement. After adding alternative geotextile reinforcement, it was found that the safety factor value increased to 1.7, where this value was greater than 1.5 as indicated by SNI 8460: 2017 article 7.5.5, while the decrease at 30 days was 1,056 cm, the decrease at 100 days was 1,056 cm, and the decline in 365 days was 1,056 cm, so it can be concluded that the embankment at that location is considered stable.